Indicator-based assessment of climate-change impacts on coasts: A review of concepts, methodological approaches and vulnerability indices. (April 2016) - Nguyen, Thang T.X.; Bonetti, Jarbas; Rogers, Kerrylee; Woodroffe, Colin D.
Abstract: Increasing human pressures on coastlines and associated threats posed by sea-level rise have stimulated development of a range of different concepts and methodological approaches to assess coastal vulnerability. The first section of this paper summarizes the concepts associated with vulnerability, natural hazards and climate change. The most widely adopted analytical approaches to vulnerability assessment are described, including spatial scales, the need for hybrid approaches comprising both biophysical and social dimensions of vulnerability, and the gradual incorporation of resilience aspects into such methodologies. In particular, the development and application of vulnerability indices is examined, based on a review of more than 50 studies that applied such indices across a range of hazards. The analytical procedures, proposed typologies, and most commonly selected variables are discussed. This overview demonstrates the breadth of vulnerability studies. This leads inevitably to lack of standardization of concepts and assumptions, which results in limited comparability between outputs for coasts from different areas. However, the widespread demand for vulnerability assessment as a component of decision-making in integrated management of the coast justifies pursuing indicator-based vulnerability assessments. In some cases these will explicitly adopt a consistent methodology that enables comparison between sites, whereas alternatively, metrics may be developed that are designed around particular system components and the site-specific functions for which they are valued. Graphical abstract: